Freezing effect on Brazil nut shelf life - Ariane Mendonça Kluczkovski; Juliana Santos Gualberto da Costa; Luiz Carlos Gomes Diogenes; Samir de Carvalho Buzaglo Pinto; Hanna Barbosa Lemos; Vanderson Gabriel Souza Torres; Augusto Kluczkovski Junior (Emirates Journal of Food and Agriculture)
The Brazil nut (Bertholletia excelsa HBK) and its derivatives hold substantial significance in the global commercial market. This seed’s edible part boasts high nutritional value despite being subject to rapid deterioration, a notable limiting factor. Recognizing the seed’s economic importance beyond its dehydrated form, this study subjected frozen Brazil nuts to two distinct freezing techniques. The physicochemical properties and stability of these nuts were evaluated at 30-day intervals for a period of six months, and the samples underwent both rapid freezing (-25 °C) and slow freezing (-18 °C) techniques before storage. Visually, the frozen Brazil nut seeds closely resembled their fresh counterparts. In terms of acidity index and peroxide index results, both methods demonstrated high efficiency, maintaining acceptable levels of conservation within the limits established by Brazilian legislation throughout the storage period. Notably, the physicochemical analyses revealed a lack of significant difference between the two freezing methods (p > 0.05), which underscores the viability of employing either technique. These findings are instructive for the food industry as they provide a potential approach for producing frozen Brazil nuts without necessitating dehydration and, as a result, they cater to consumers desiring to enjoy the distinctive characteristics of this seed.